VD_FINDINFO Arrêt / 2020 / 764 vom 15. September 2020 - VD Tribunal cantonal (2020)
NOUVELLE DEMANDE, MOTIF DE RÉVISION, RENTE D'INVALIDITÉ, ADMISSION PARTIELLE | 28 al. 1 LAI, 29 al. 1 LAI, 17 LPGA, 87 al. 2 RAI, 87 al. 3 RAI